Coordinate control of syntheses of ribosomal ribonucleic acid and ribosomal proteins during nutritional shift-up in Saccharomyces cerevisiae. - Kief, D R (1981)
We investigated the regulation of ribosome synthesis in Saccharomyces cerevisiae growing at different rates and in response to a growth stimulus. The ribosome content and the rates of synthesis of ribosomal ribonucleic acid and of ribosomal proteins were compared in cultures growing in minimal medium with either glucose or ethanol as a carbon source. The results demonstrated that ribosome content is proportional to growth rate. Moreover, these steady-state concentrations are regulated at the level of synthesis of ribosomal precursor ribonucleic acid and of ribosomal proteins. When cultures growing on ethanol were enriched with glucose, the rate of ribosomal ribonucleic acid synthesis, measured by pulsing cells with [methyl-3H]methionine, increased by 40% within 5 min, doubled within 15 min, and reached a steady state characteristic of the new growth medium by 30 min. Labeling with [3H]leucine reveal a coordinate increase in the rate of synthesis of 30 or more ribosomal proteins as compared with that of total cellular proteins. Their synthesis was stimulated approximately 2.5-fold within 15 min and nearly 4-fold within 60 min. The data suggest that S. cerevisiae responds to a growth stimulus by preferential stimulation of the synthesis of ribosomal ribonucleic acid and ribosomal proteins.